Respon Siswa Terhadap Modul Elektronik Subkonsep Sistem Peredaran Darah Manusia Berbasis Problem Based Learning - Nazara, Ainal Wazni; Halang, Bunda; Rezeki, Amalia (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Online learning has obstacles, including the lack of interaction between students and teachers which causes students to become bored with monotonous learning. The concept of the circulatory system is a complex material, so it requires varied teaching materials such as problem-based learning-based electronic modules that can improve mastery of sub-concepts and help students learn independently. PBL-based electronic modules can improve student learning outcomes and electronic modules can support the learning objectives to be achieved. This study aims to describe student responses to the developed electronics module. The research method used is Research and Development in the form of a 4D model consisting of the define, design, develop, and disseminate stages which are modified only until the develop stage. The subject of the response test consisted of 9 students of class XI MIPA SMAN 4 Banjarbaru. The results of the research on the developed PBL-based electronic module obtained a student response test score of 4.58 in a very positive category which indicates that the developed electronic module has a very positive impact on students.